Hobson's choice [videorecording (DVD)] - Lean, David, 1908-1991; Lean, David, 1908-1991; Lean, David, 1908-1991; Laughton, Charles, 1899-1962; Mills, John, 1908-2005; De Banzie, Brenda, 1915-1981; Anderson, Daphne, 1922-2013; Tomelty, Joseph, 1910-1995; Scales, Prunella; Brighouse, Harold, 1882-1958 (Criterion collection, 2008)
An owner of a Victorian-era boot shop finds himself in a battle of wills with his headstrong eldest daughter, who wants to make her own professional and personal decisions in her life.